Evaluation of teachers' feedback quality in English language instruction at secondary schools - Arrafii, Moh. Arsyad; Kasyfurrahman (Journal of English Language Proficiency, 2024)
Feedback is crucial aspect of instruction and teacher understanding of feedback determine the quality of practices in classroom. This study involved four English teachers who teach at a public secondary school in Central Lombok Regency, Indonesia. Interviews were conducted with these teachers to investigate their theoretical understanding of feedback, and classroom observations were carried out to observe and evaluate their feedback practices. Analysis reveals that the teachers’ theoretical understanding of feedback and its typologies remains very limited. Teachers still struggle to formulate a conceptual or operational definition that underlines effective feedback. The study also indicates that the teachers’ ability to deliver feedback is not yet optimal. This is evident from the nature of the feedback provided, which remains very general, without detailed descriptions of students’ achievements that could serve as references for students to improve their performance. The quality of teacher feedback to students is still largely normative, consisting primarily of verbal praise, symbols, and approving expressions. Although there are efforts to enhance individual consultations and two-way dialogue with students, these efforts are not fully realized and tend to overlook other students, as teachers focus only on the students they are engaging with in dialogue. These findings are consistent with results from previous studies.